2019
DOI: 10.1111/and.13319
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of tamsulosin combined with dapoxetine in management of type III prostatitis with premature ejaculation

Abstract: To evaluate the efficacy and safety of tamsulosin combined with dapoxetine in the treatment of type IIIB chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) that is complicated by premature ejaculation (PE), a total of 251 CP/CPPS patients with PE were recruited from nine hospitals across China and were randomly divided into two groups: one received tamsulosin as a control, and the other received a combination therapy of tamsulosin and dapoxetine. Follow‐up was conducted at four time points, and indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Smooth muscle contraction during ejaculation may increase the symptoms of CP. In addition, decreased pelvic region blood flow and ischemia in the pathophysiology of CP/CPPS cause damage to the nerves innervating the pelvic region, which may trigger PE [26]. In our study, it was observed that ESWT treatment reduced pain in the pelvic region, reduced LUTS, and improved both erectile functions and PE symptoms in LUTS, as it provided the regeneration of nerves in the pelvic region.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Smooth muscle contraction during ejaculation may increase the symptoms of CP. In addition, decreased pelvic region blood flow and ischemia in the pathophysiology of CP/CPPS cause damage to the nerves innervating the pelvic region, which may trigger PE [26]. In our study, it was observed that ESWT treatment reduced pain in the pelvic region, reduced LUTS, and improved both erectile functions and PE symptoms in LUTS, as it provided the regeneration of nerves in the pelvic region.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, treatments for PE due to CP/CPPS focused on classical antibiotic, anti-inflammatory, and alpha- blocker treatments. One study showed that the use of dapoxetine in combination with the alpha-blocker tamsulosin had a significant curative effect on IELT and PEP scores [26].…”
Section: Discussionmentioning
confidence: 99%
“…Following abstract screening and full-text reviews, 25 randomised controlled trials involving 3514 patients with CP/CPPS were included ( Figure 1 ). 9 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Overall, the studies were conducted between 1999 and 2019. For the analysis, we compared 18 monotherapies, six combination therapies and placebo.…”
Section: Resultsmentioning
confidence: 99%
“…The excitability of the bladder neck, urethra, and smooth muscle of the prostate can be selectively inhibited by α-adrenergic receptor blockers (α-ARBs), which can reduce the obstruction of the position of the urethra by promoting muscle relaxation and alleviating urethral obstruction (5,6). In recent years, the effects of α-ARBs such as alfurazosin, tamsulosin, and terazosin in the treatment of type III Original Article Systematic review and meta-analysis: α-adrenergic receptor blockers in chronic prostatitis prostatitis has been confirmed by many domestic and foreign scholars (7)(8)(9). However, current clinical studies on the treatment of CP with α-ARBs have different results and are of varying quality, using different scales and measuring different effects.…”
Section: Introductionmentioning
confidence: 99%